The Role of Communication Leaders in Planning and Acceleration of Development In Tanjung Alam Sei Dadap Asahan Village - Dailami, Dailami; Wahyuni, Sri; Wiranti , Arinda (Kirana Publisher (KNPub), 2022)
This study aims to determine the role of communication from community leaders in development planning including the construction of village roads, the development of drinking water sources, the National Community Empowerment Program (PNPM) Mandiri, the preservation of community traditions and the construction of mosques. in Tanjung Alam Village, Sei Dadap District, Asahan District. Participation of community leaders is involvement carried out by non-formal circles. When talking about the community, it means talking about the community itself, community leaders are representatives of the village community. In this study, researchers used descriptive qualitative research with data collection techniques through interviews, observation and documentation. There were 7 informants in this study taken using a purposive sampling technique, including the Head of Tanjung Alam Village, 2 community leaders of Tanjung Alam and 4 members of the Tanjung Alam Village community. The researcher used an interactive data analysis model to describe the results of the research into a data analysis technique and to check the validity of the researcher's data using a triangulation technique. The focus of this research is the communication role of Community Leaders in development planning in Tanjung Alam Village. The data analysis technique used in this study is descriptive qualitative, namely collecting data by conducting interviews with related parties. The results of the research show that the role of communication of community leaders is to increase knowledge in development so that development planning is carried out by referring to applicable regulations, and upholding community ethics and values .